A Seaweed Extract-Based Biostimulant Mitigates Drought Stress in Sugarcane - Jacomassi, Lucas Moraes; Viveiros, Josiane de Oliveira; Oliveira, Marcela Pacola; Momesso, Letusa; de Siqueira, Gabriela Ferraz; Crusciol, Carlos Alexandre Costa (Frontiers in Plant Science, 2022)
Drought is one of the most important abiotic stresses responsible for reduced crop yields. Drought stress induces morphological and physiological changes in plants and severely impacts plant metabolism due to cellular oxidative stress, even in C4 crops such as sugarcane. Seaweed extract-based biostimulants can mitigate negative plant responses caused by drought stress. However, the effects of foliar application of such biostimulants on sugarcane exposed to drought stress, particularly on plant metabolism, stalk and sugar yields, juice purity and sugarcane technological quality, have received little attention. Accordingly, this study aimed to evaluate the effects of foliar application of a seaweed extract-based biostimulant on late-harvest sugarcane during the driest period of the year. Three experiments were implemented in commercial sugarcane fields in Brazil in the 2018 (site 1), 2019 (site 2) and 2020 (site 3) harvest seasons. The treatments consisted of the application and no application of seaweed extract (SWE) as a foliar biostimulant in June (sites 2 and 3) or July (site 1). The treatments were applied to the fourth ratoon of sugarcane variety RB855536 at site 1 and the fifth and third ratoons of sugarcane variety SP803290 at sites 2 and 3, respectively. SWE was applied at a dose of 500 mL a.i. ha-1 in a water volume of 100 L ha-1. SWE mitigated the negative effects of drought stress and increased stalk yield per hectare by up to 3.08 Mg ha-1. In addition, SWE increased stalk sucrose accumulation, resulting in an increase in sugar yield of 3.4 kg Mg -1 per hectare and higher industrial quality of the raw material. In SWE-treated plants, Trolox-equivalent antioxidant capacity and antioxidant enzyme activity increased, while malondialdehyde (MDA) levels decreased. Leaf analysis showed that SWE application efficiently improved metabolic activity, as evidenced by a decrease in carbohydrate reserve levels in leaves and an increase in total sugars. By positively stabilizing the plant’s cellular redox balance, SWE increased biomass production, resulting in an increase in energy generation. Thus, foliar SWE application can alleviate drought stress while enhancing sugarcane development, stalk yield, sugar production, and plant physiological and enzymatic processes.